2015
DOI: 10.1098/rstb.2014.0233
|View full text |Cite
|
Sign up to set email alerts
|

Species differences in tumour responses to cancer chemotherapy

Abstract: Despite advances in chemotherapy, radiotherapy and targeted drug development, cancer remains a disease of high morbidity and mortality. The treatment of human cancer patients with chemotherapy has become commonplace and accepted over the past 100 years. In recent years, and with a similar incidence of cancer to people, the use of cancer chemotherapy drugs in veterinary patients such as the dog has also become accepted clinical practice. The poor predictability of tumour responses to cancer chemotherapy drugs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 132 publications
(162 reference statements)
0
16
0
3
Order By: Relevance
“…Therefore, compared to other animals, canines have been proposed to be a good model for cancer research, and development of therapeutic drugs and next-generation radiotherapies [10, 25, 30]. Previous studies in human and rodent cells have shown that the localization and function of Ku70 at DSB sites might play a crucial role in modulating the NHEJ repair pathway [3, 14, 20, 26, 28].…”
mentioning
confidence: 99%
“…Therefore, compared to other animals, canines have been proposed to be a good model for cancer research, and development of therapeutic drugs and next-generation radiotherapies [10, 25, 30]. Previous studies in human and rodent cells have shown that the localization and function of Ku70 at DSB sites might play a crucial role in modulating the NHEJ repair pathway [3, 14, 20, 26, 28].…”
mentioning
confidence: 99%
“…Vielleicht sind diese Artikel auch für Humanmediziner lesenswert, werden doch spontan beim Hund auftretende Tumoren immer wieder (wenn auch kontrovers) als «Modell» für humane Tumorerkrankungen diskutiert [13]. Zudem ist in der Tiermedizin an der Tagesordnung, was in der Humanmedizin selten bis undenkbar ist, nämlich der ausdrückliche Wunsch des Tierbesitzers (mithin nach operativer Entfernung des Tumors), auf weitere Therapien zu verzichten.…”
Section: Tumorerkrankungen Beim Tierunclassified
“…Man mag das verteufeln oder für eine herausragende Errungenschaft der modernen medizinischen Forschung halten. Aber selbst wenn der Nutzten solcher Studien nicht unumstritten ist [13]: Fakt ist, dass derzeit die rechtlichen Rahmenbedingungen solche Versuche schlicht unumgänglich machen und dass überwiegend diese Art von Forschung Erkenntnisse über grundsätzliche Wirkmechanismen ermöglicht.…”
Section: Tumorerkrankungen Beim Tierunclassified
See 1 more Smart Citation
“…Among the other non‐contagious diseases, cancer seems to be a leading cause of morbidity and mortality, and some estimation has predicted that there will be 13.1 million deaths because of cancer in 2030 . Chemotherapy is the most popular therapeutic strategy for patients with cancer . However, as most of the currently used chemotherapeutic agents do have severe toxic effects, which may cause limitations in their usage, it would be worthwhile to consider having therapeutic agents that simultaneously have improved efficacy and less toxicity.…”
Section: Introductionmentioning
confidence: 99%